Badagoy Irrigation Association Inc. - Remonde, Roxan G. (School of Management, University of the Philippines Mindanao, 2011)
This strategic paper is a vehicle in determining the best possible strategy for Badagoy Irrigation Association Inc., being the sole water irrigation system in Magsaysay, Davao del Sur. Badagoy Irrigation Association is the largest irrigation system of its kind in the Philippines; Badagoy is a landmark in the country?s settling of Communal Irrigation Systems. The 2,250 hectares of service area stretches across eight (8) barangays like a never-ending sight of lush green carpel. The conceptual framework used for the study is an adapted from Fred R. David (2008) conceptual framework. The Badagoy Irrigation system aims to help the farmers? livelihood. They aim to create a sustainable water supply, which will increase their agricultural products? yield. This Strategic Plan will help the BIA achieve its intended result; larger irrigated areas, greater productivity, stronger associations, improved water distribution, better compliance with government policies, and improved relations between government and farmers. In order to attain the goals of the Badagoy Irrigation Association, the writer used the conceptual framework adapted from Dr. Fred R. David, 2008 to set the long-range direction of the organization. This would analyze and undertake the annual environmental and financial assessment of current and future factors likely to impact Badagoy?s fulfillment of its mission and vision. Such assessment will include derived conclusions, identified potential consequences or scenarios, and suggested strategic responses. This will support the preparation of Badagoy?s Yearly Operational Plan, which flows from this Strategic Plan. This will also support preparation of the Budget for Badagoy?s next fiscal year, which is developed from the Operational Plan. It is a continuous cycle for the Badagoy to assess and review for them to be highly adaptive to any innovative change.